4 Deactivation of implantable cardioverter defibrillatorsin end-of-life situations – a single centre experience. (16th October 2019) - Nolan, P; Smyth, Y; Nash, P; Crowley, J; McNeill, B
Abstract : Background: Implantable Cardioverter Defibrillators (ICDs) have been proven to reduce the incidence of sudden cardiac death in both primary and secondary prevention populations. However, it is recognised that shock treatment can be negatively experienced by patients and there is recognition that this may be inappropriate in end-of-life and palliative care situations. Despite the fact that both Heart Rhythm Society and European Heart Rhythm Association Consensus documents both outline the appropriateness of deactivation of ICD shock therapy in these situations, research has shown that 27% of patients receive shock therapy in the last month of life (Goldstein et al 2004). Aim: The aim of the study was report on the single centre experiences of a protocol for deactivation of ICDs and Cardiac Resynchronisation Therapy Defibrillators (CRT-Ds) in a large tertiary referral centre. Methods: This large tertiary referral centre has had a protocol for Deactivation of ICDs in End-of-Life Situations since late 2009 (figure 1 ). ICD and CRT-D records for patients implanted in this centre were analysed for deaths which occurred between Jan 2010 and Dec 2018. Follow-up records were analysed for devices which were deactivated prior to death. Results: A total of 149 patients with ICDs or CRT-Ds died between Jan 2010 and Dec 2018 which represented 23.8% of the ICD and CRT-D population implanted in the centre. 44 patients had the shock therapy of their device deactivated prior to death. This represented 29.4% of the patients with ICDs or CRT-Ds who died during this period. The numbers of deactivations are showing an upward trend, from one deactivation in 2010 to twelve deactivations in 2018 (figure 2 ). Of these 44 patients, device deactivation occurred in the following locations 79% in the implanting centre 11.9% in the patients home or nursing home 6.8% in hospice settings 2.3% in an outlying hospital It was noted that the family were present at the time of deactivation in 32% of cases. All deactivations occurred less than 7 days from the date of the patient's death. All were carried out by Cardiac physiologists and performed in less than 24 hours. Where deactivation occurred in the community, the Cardiac Physiologist was met by a palliative care nurse or GP. In one case the hospital Heart Failure Nurse travelled with the Cardiac Physiologist. In two further cases, requests for deactivation were received but could not be acted upon before the patient's death. Both of these cases were from the community. Conclusion: Deactivation of shock therapy in ICDs and CRT-Ds in end-of life situations is increasing and this service can be delivered by Cardiac Physiologists. Whilst the vast majority of deactivations occur in the implanting centre, over one in five occur in other settings and services should be designed to meet this need. The fact that only 29.4% of patients with ICDs or CRT-Ds implanted had their device deactivated, coupled with the fact that all deactivations occurred less than 7 days prior to date of death, suggest that significant education around this issue with other healthcare providers needs to take place.